Nanofluids for flat plate solar collectors: Fundamentals and applications. (1st April 2021) - Alawi, Omer A.; Kamar, Haslinda Mohamed; Mallah, A.R.; Mohammed, Hussein A.; Kazi, S.N.; Che Sidik, Nor Azwadi; Najafi, Gholamhassan
Abstract: Among different sources of renewable energy, solar energy is widely used almost exclusively because of its ease of availability and its lowest environmental effects. The most commonly used solar collectors are the flat plate solar collectors (FPSCs). However, they are less powerful (low capacity to convert solar energy to thermal energy). It is possible to classify the use of nanofluid on FPSCs as an efficient way to boost the solar collectors' performance. In this paper, studies on metal oxides, non-metal oxides, solid metals, semiconductor nanomaterials, carbon nanostructured, and nanocomposite nanofluids used as heat transfer fluids (HTFs) within FPSCs are examined sequentially. Various parameters affecting the FPSC's thermal efficiency, such as nanoparticle type, nanoparticle concentration, nanoparticle size/shape, solar radiance, and mass flow rate, are extensively analyzed. Studies have also compared various types of single nanofluids or mixture nanofluids with FPSCs under the same operating conditions. It is found that the use of carbon-based nanofluids compared to metal oxides of nanofluids under the same conditions has resulted in a major improvement in the energetic and exergetic performance of the FPSC. Furthermore, the reviewed research revealed that there is a tremendous opportunity to achieve the commercial application of carbon-based nanofluid FPSC. The obstacles and opportunities for further study are also highlighted.